2019
DOI: 10.35940/ijrte.d4378.118419
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Deep Neural Network Based Clinical Decision Support System for the Determination of Fetal Health

Abstract: Healthcare industry is undergoing changes at a tremendous rate due to healthcare innovations. Predictive analytics is increasingly being used to diagnose the patient’s ailments and provide actionable insights into already existing healthcare data. The paper looks at a decision support system for determining the health status of the foetus from cardiotographic data using deep learning neural networks. The foetal health records are classified as normal, suspect and pathological. As the multiclass cardiotographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…He observed that the SVM model outperformed the others with an F1 score of 93% and an accuracy of 81%. He also reported that the DNN model had higher performance than SVM, with a G-mean of 91% and a sensitivity of 89% [38].…”
Section: Discussionmentioning
confidence: 99%
“…He observed that the SVM model outperformed the others with an F1 score of 93% and an accuracy of 81%. He also reported that the DNN model had higher performance than SVM, with a G-mean of 91% and a sensitivity of 89% [38].…”
Section: Discussionmentioning
confidence: 99%
“…Vani conducted an experiment on a decision support system using DL-based neural networks to determine the health status of fetuses from the CTG dataset (86). They used the CTG dataset with 21 features and 2126 examples and used SVM and DNN models with a ratio of 0.7:0.3 for training and testing.…”
Section: Potharaju Et Al Aimed To Improve the Classification Accuracy...mentioning
confidence: 99%